Letter from Paul Baudoüin to Marguerite Lemercier, mentioning a suscription to her project, - Baudoüin, Paul Albert, 1844-1931 (1922)
Author mentions that, while he understand the publication of "Lettres d'un soldat" and the "album" with André Michel's foreword, he does not see the point of "Lettres d'un soldat" with new letters and notes as it would become an illustrated book.